2021
DOI: 10.1039/d0na00826e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic gas sensing: working principles and recent developments

Abstract: Gas sensors work on the principle of transforming the gas adsorption effects on the surface of active material into the detectable signal in terms of its changed electrical, optical, thermal,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Magnetic gas sensors have gained popularity in recent times due to their safety and lack of electrical contacts. [71][72][73] Hence, the prospect of GaAs monolayer as a magnetic gas sensor has been explored. Spin-polarized DFT calculations were performed to analyze the magnetic moment of the gas adsorbed systems.…”
Section: Gas Sensing Performance Of Gaas Monolayermentioning
confidence: 99%
“…Magnetic gas sensors have gained popularity in recent times due to their safety and lack of electrical contacts. [71][72][73] Hence, the prospect of GaAs monolayer as a magnetic gas sensor has been explored. Spin-polarized DFT calculations were performed to analyze the magnetic moment of the gas adsorbed systems.…”
Section: Gas Sensing Performance Of Gaas Monolayermentioning
confidence: 99%
“…It was found in [90] that thinner film samples would be more suitable for sensing applications because of their higher surface-to-volume ratio and since the absolute value of the measured signal increases when the film thickness is decreased. This proposed concept has been followed [14,70,[108][109][110][111][112][113] and its feasibility was further confirmed by demonstrations of detection of low concentration of H 2 using thin Pd/Co films as the sensor material [70,90,109,114,115]. In particular, it was shown that the EHE sensitivity of optimised samples could exceed 240% per 104 ppm at H 2 concentrations below 0.5% in the N 2 /H 2 atmosphere [90], thus providing a more than two orders of magnitude higher sensitivity compared with the competing resistivity-based sensor architectures.…”
Section: Magneto-electronic Hydrogen Sensors Based On the Magneto-opt...mentioning
confidence: 99%
“…This urges the development of new hydrogen sensors designed to meet the demands of the emergent hydrogen economy. The literature summarising and discussing the recent progress in this rapidly growing research field is abundant (for a review see, e.g., [9][10][11][12][13][14]), and thus the reader is referred to those articles for further details. However, despite significant advances made in this area, most of the hydrogen gas sensor concepts proposed thus far have several major drawbacks, including poor sensitivity, complex detection systems, slow response time, high power consumption and potential flammability issues [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…The gas-sensing system is important in various applications including industrial pollutant gas leakage detection, environmental monitoring, medical care, food industry, etc. [ 1 ]. Nanomaterials show great performance in this field of technology [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the most effective materials for gas sensing belong to the groups of metal-organic framework-based nanostructured materials [ 3 , 4 ] and low-dimensional materials [ 5 , 6 ]. Another type of sensor is based on magnonic sensors with the presence of magnetic nanoparticles [ 7 ] and two-dimensional materials [ 1 , 8 ] and it seems to be promising for further development.…”
Section: Introductionmentioning
confidence: 99%